The 15 invaluable laws of growth [compact disc, unabridged] : live them and reach your potential - Maxwell, John C., 1947- (Hachette Audio, 2012)
Are there tried and true principles that are always certain to help a person grow? John Maxwell says the answer is yes. He teaches listeners everything he has gleaned about what it takes to reach their potential.